INOVASI TERINTEGRASI DALAM PELAYANAN PUBLIK DI ERA OTONOMI DAERAH - Martateri, Martateri (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2017)
This paper analyzes the problems in public service within the framework of regional autonomy. As we know that regional autonomy has different designs in decades of government leadership, ranging from old order, new order and reform. Differences paradigm and understanding of the implementation model of regional autonomy, it can not be separated from the different public service system that occurs. This paper focuses on the development of regional autonomy and the public service in the entry period of reform, in which many changes in the legal instruments of local government administration, especially in relation to the laws and regulations related to regional government. The development of regional autonomy patterns based on the public service model in the region and its development through one get service, as an incentive to create public service standards. This study aims to map out public service models by local governments and by using qualitative methods with a literary approach (liberary reaserch)Public Service,